Penggunaan Aplikasi Kesehatan untuk Media Edukasi Kesehatan pada Ibu Hamil: Narrative Review - Ermiati, Ermiati; Suherman, Ara Ardiansah; Cahyani, Regina; Putri, Maria Ulpa Ananda; Parwati, Hanny Cindi; Rahmawati, Nur Rini; Khalam, Sadarul; Srimurni, Nita Ayu (Universitas Malahayati, 2024)
ABSTRACT The development of digital technology, especially mobile applications, has brought significant changes in health information and services. Mobile applications can be very effective tools for disseminating knowledge, providing support, and increasing awareness about health care during pregnancy. The purpose of this literature review is to explore applications as educational media for pregnant women. The narrative review approach was used with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The databases used included PubMed and Google Scholar as search engines. The researchers obtained 63 articles, which were then screened with inclusion criteria of publications from 2015-2023, free full-text articles, RCT design, and written in English and Indonesian, resulting in 10 suitable articles. The analysis of 10 articles found several applications that can increase knowledge for pregnant women, namely the M-Health application, HealthyMoms, Danger Signs of Pregnancy (TABAMIL), Health-e Babies, Smarter Pregnancy, Self-Care Mobile for Pregnant Women at Work, and The Asian Parents. The use of health applications has proven to be useful in increasing pregnant women's knowledge, exclusive breastfeeding, mothers' behavior regarding chronic energy deficiency, danger signs of pregnancy, and healthy lifestyles for pregnant women. Future research is recommended using a multidisciplinary approach, longitudinal studies, RCTs, and qualitative analysis, as well as expanding the study population to understand the experiences of users from various backgrounds, while ensuring the suitability of the application to the information needs of pregnant women in the community who collaborate with health workers for service integration. Keywords: Health Education, Mobile Application, Pregnant Woman ABSTRAK Perkembangan teknologi digital khususnya aplikasi mobile, telah membawa perubahan signifikan dalam informasi dan layanan kesehatan. Aplikasi mobile dapat menjadi alat yang sangat efektif untuk menyebarkan pengetahuan, memberikan dukungan, dan meningkatkan kesadaran tentang perawatan kesehatan selama masa kehamilan. Tujuan dari tinjauan literatur ini untuk mengeksplorasi aplikasi sebagai media edukasi kesehatan pada ibu hamil. Pendekatan narrative review dengan pemilihan artikel dengan panduan Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Database yang digunakan terdiri dari PubMed dan Google Scholar sebagai saerch engine. Peneliti mendapatkan 63 artikel yang selanjutnya dilakukan skrining dengan kriteria inklusi yaitu publikasi tahun 2015-2023, artikel free full text, desain RCT, serta berbahasa Inggris dan Indonesia sehingga didapatkan 10 artikel yang sesuai. Hasil analisis 10 artikel ditemukan beberapa aplikasi yang dapat meningkatkan pengetahuan bagi ibu hamil yaitu aplikasi M-Health, HealthyMoms, Tanda Bahaya Kehamilan (TABAMIL), Health-e Babies, Smarter Pregnancy, Self-Care Mobile for Pregnant Women at Work, dan The Asian Parent. Penggunaan aplikasi kesehatan terbukti bermanfaat dalam meningkatkan pengetahuan ibu hamil, ASI eksklusif, perilaku ibu tentang kekurangan energi kronis, tanda bahaya kehamilan, dan pola hidup sehat bagi ibu hamil. Penelitian selanjutnya disarankan menggunakan pendekatan multidisiplin, studi longitudinal, RCT, dan analisis kualitatif, serta memperluas populasi studi untuk memahami pengalaman pengguna dari berbagai latar belakang, sambil memastikan kesesuaian aplikasi dengan kebutuhan informasi ibu hamil di lingkungan masyarakat yang bekerja sama dengan tenaga kesehatan untuk integrasi layanan. Kata Kunci: Aplikasi Mobile, Pendidikan Kesehatan, Wanita Hamil